Downregulation of miR-493 promoted melanoma proliferation by suppressing IRS4 expression - Aili Cui; Zhehu Jin; Zhonggao Gao; Mingji Jin; Lianhua Zhu; Lianhua Li; Chenglong Jin; Yinghua An (Tumor Biology, 2017)
Accumulating evidence indicated that aberrantly expressed microRNAs play critical roles in the initiation and progression of human cancers. However, the underlying functions of miR-493 in human melanoma remains unknown. Here, our study found that miR-493 expression was downregulated in human melanoma tissues and cells. Overexpression of miR-493 suppressed cell proliferation and cell cycle in human melanoma cell line A375. IRS4 was defined as a target for downregulation by miR-493 and was confirmed by luciferase assay. We also found that knockdown of IRS4 counteracted the proliferation promotion by miR-493 inhibitor. In summary, these results demonstrated that miR-493 acts as a tumor suppressor and inhibits cell proliferation and cell cycle in human melanoma by directly targeting IRS4.